Decision-making and techniques in hypogastric artery revascularization - Geisbüsch, Philipp; Attigah, Nicolas; Hyhlik-Dürr, Alexander; Hakimi, Maani; Müller-Eschner, Matthias; Böckler, Dittmar (The journal of cardiovascular surgery, 2013)
The aim of this article was to describe and discuss the currently available endovascular and open surgical techniques to preserve or occlude the hypogastric artery during aortoiliac aneurysm repair and thus support the process of decision-making in hypogastric artery revascularization.
Gesehen am 03.02.2020
DOI nicht ermittelbar, Verlinkung via DOI nicht möglich